Using Drones in a Warehouse with Minimum Energy Consumption - Derpich-Contreras, I; Sepulveda-Salas, J (Institute of Electrical and Electronics Engineers Inc., 2018)
In this paper we analyze the feasibility of using drones in a manufacturing factory that requires multiple transports from the warehouse to the workstations. Considering low cost drones it is understood that they have little autonomy and low load capacity. To minimize energy consumption a mathematical model of vehicle routing type is used, in three dimensions, which is solved using a heuristic method based on the structure of the problem. The problem is complex because the routes must be planned in order to avoid collisions, therefore they must follow time windows in the deliveries. © 2018 IEEE.